Lateral detrital C transfer across a Spartina alterniflora invaded estuarine wetland - Yu Gao (SpringerOpen, 2021)
Abstract Background The lateral movements of mass and energy across the terrestrial-aquatic interface are being increasingly recognized for their importance in the carbon (C) balance of coastal/estuarine wetlands. We quantified the lateral flux of detrital C in the Yangtze estuary where invasive Spartina alterniflora has substantially and extensively altered the ecosystem structure and functions. Our overall objective was to close the C budget of estuarine wetlands through field sampling, tower-based measurements, and modeling. Methods A lateral detrital C exchange evaluation platform was established in a case study of the Yangtze River Estuary to investigate the effect of ecosystem structural changes on lateral detrital C transfer processes. This study estimated the lateral detrital C exchange based on the gross primary production (GPP) by performing coupled modeling and field sampling. Tower-based measurements and MODIS time series and CH4 outgassing and biomass simultaneously measured the lateral detrital C flux to characterize the relative contributions of lateral (i.e., detritus) C fluxes to the annual marsh C budget. Results The C pools in the plants and soil of Spartina marshes were significantly higher than those of the native community dominated by Phragmites australis. The GPP based on MODIS (GPPMODIS) was 472.6 g C m−2 year−1 and accounted for 73.0% of the GPP estimated from eddy covariance towers (GPPEC) (646.9 ± 70.7 g C m−2 year−1). We also detected a higher GPPMODIS during the pre-growing season, which exhibited a similar lateral detrital C flux magnitude. On average, 25.8% of the net primary production (NPP), which ranged from 0.21 to 0.30 kg C m−2 year−1, was exported during lateral exchange. The annual C loss as CH4 was estimated to be 17.9 ± 3.7 g C m−2 year−1, accounting for 2.8% of the GPPEC. The net positive detrital C flux (i.e., more detritus leaving the wetlands), which could exceed 0.16 kg C m−2 day−1, was related to daily tides. However, the observed lateral detrital C flux based on monthly sampling was 73.5% higher than that based on daily sampling (i.e., the sum of daily sampling), particularly in March and October. In addition, spatiotemporal granularities were responsible for most of the uncertainty in the lateral detrital C exchange. Conclusion This research demonstrated that an integrated framework incorporating modeling and field sampling can quantitatively assess lateral detrital C transport processes across the terrestrial-aquatic interface in estuarine wetlands. However, we note some limitations in the application of the light-use efficiency model to tidal wetlands. Spartina invasion can turn the lateral C balance from a C source (209.0 g C m−2 year−1) of Phragmites-dominated marshes into a small C sink (-31.0 g C m−2 year−1). Sampling over a more extended period and continuous measurements are essential for determining the contribution of different lateral detrital C flux processes to closing the ecosystem C budgets. The sampling spatiotemporal granularities can be key to assessing lateral detrital C transfer.